“How Do I Love Thee?” and “Meeting At Night”: An Inter-Textual of The Transposition Meaning Analysis - Tiwiyanti, Leni; Sofiani, Yulia; Passandaran, Yosi M. (Pujangga, 2025)
This research aims to describe the intertextuality between Elizabeth Barrett Browning's “How Do I Love Thee?” and Robert Browning's “Meeting at Night”. The focus of the present research are on how the two texts interact with one another in terms of style, theme, and linguistic structure. The study combines qualitative and descriptive methodologies, combined with Julia Kristeva's intertextual analysis. In relation to the research's findings, the intertextual relationship between the two poems not only deepens our comprehension of each author's work but also presents the dynamics of the personal and creative relationship between them. By using intertext theory by Kristeva, researchers found that both poems use transpositions to explore various interpretations and experiences of love, reflecting the poets’ individual styles and cultural contexts. In hypogram, Barrett Browning uses linguistic structures such as anaphora, repetition, and abstract language to create a contemplative atmosphere, emphasizing love's sacred nature. Therefore, this research does not only offer fresh perspectives on how the Brownings discussed their private lives but also cultivates a creative conversation that enhanced Victorian English literature's portrayal of love. It is anticipated that this research will further our understanding of how love is socially and culturally constructed in literary works and advance the field of inter-textual research.